2017
DOI: 10.1089/jpm.2016.0272
|View full text |Cite
|
Sign up to set email alerts
|

Health System Advance Care Planning Culture Change for High-Risk Patients: The Promise and Challenges of Engaging Providers, Patients, and Families in Systematic Advance Care Planning

Abstract: We learned that changing culture and systems to promote ACP requires a comprehensive vision with simultaneous, interconnected strategies targeting patient education, clinician training, EMR documentation, and community awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…11 Before the intervention, special ACP training was offered to alleviate the fear and avoidance of ACP topics among nursing students. Reidy et al 12 designed an Internet-based APC training and promotion tool based on the local primary health-care system and 2 specialist clinics. As a result, 85% of 807 registrants developed ACP, of which 583 were medical staff and medical students.…”
Section: Discussionmentioning
confidence: 99%
“…11 Before the intervention, special ACP training was offered to alleviate the fear and avoidance of ACP topics among nursing students. Reidy et al 12 designed an Internet-based APC training and promotion tool based on the local primary health-care system and 2 specialist clinics. As a result, 85% of 807 registrants developed ACP, of which 583 were medical staff and medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Changing culture and implementing new ways of working like with AAC requires a comprehensive vision with simultaneous, interconnected strategies targeting clinician training (Reidy et al., ). Research has shown how communication in the care of patients with advanced and serious illnesses can be improved using interventions, particularly with regard to healthcare use (Fawole et al., , 570–577).…”
Section: Discussionmentioning
confidence: 99%
“…Changing culture and implementing new ways of working like with AAC requires a comprehensive vision with simultaneous, interconnected strategies targeting clinician training (Reidy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Care Connect Program and the Conversation Project are patient navigatorled ACP programs implemented by health systems in Alabama and Wisconsin, respectively. 36,37 Care manager and navigator roles are tailored based on the patient population, health system or insurer goals, and resources available. As a result, there is significant variability in their parameters, including scope of practice.…”
Section: Tip 6: Clinical Decision Support Tools Can Help To Further Tmentioning
confidence: 99%